Perancangan Antarmuka Web Access Dwelling Time Menggunakan Metode Human Centered Design (HCD) Pada Kantor Pengawasan dan Pelayanan Bea dan Cukai (KPPBC) Tipe Madya Pabean (TMP) Tanjung Perak Kota Surabaya - Fauzizah Andriani; Yusi Tyroni Mursityo; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The general directorate of custome and excise is an institution which has a branch office in different cities across Indonesia. The head office of custom and excise in east Jakarta records all import goods and those data are distributed to the brance offices and excise that exist. The information which made by the management are not able to be a proponent decision because they are still in the form of table. Dwelling time is the time it takes imported goods that is heaped up in the temporary landfill port since freight out of the ship to be removed. The plan of the usage of Human Centered Design (HCD) method is to understand the needs of users and real difficulties to be faced by. HCD get users divided into two categories common admin and users .Unlike public users can only see dashboard course, admin have need more to manage the data if there are the latest data .Needs made UML defined and wireframe to get the system .Design implemented into the system needs tested to ensure is in accordance with expected users .Results obtained design with the HCD produce a web access dwelling time to display information importation goods in one screen as the need is defined and improve the efficiency time when it update.